Managerial implications of student activity information system implementation at Faculty of Business and Management / Norshima Humadi - Humadi, Norshima; Jaafar, Muhamad Sukor; Shahrom, Melissa; Shariff, Siti Halijjah (Universiti Teknologi MARA Cawangan Sarawak, 2020)
Faculty of Business and Management – Student Activity Information System (FBM-SAIS) was developed with an aim to manage the student activity application process effectively through the Internet. This study was conducted to determine the managerial implications of FBM-SAIS implementation to FBM, UiTM Selangor by focusing on the manpower and financial impact, as well as to determine the direct effect of SAIS Service Quality on SAIS student satisfaction. This study proposed SAIS Service Quality as a higher-order factor in order to determine a direct effect of SAIS Service Quality on student satisfaction towards SAIS implementation. Interviews were conducted to identify the managerial implications of student activity application process before and after SAIS implementation. Meanwhile, the quantitative data was gathered from 94 SAIS users who were FBM students through e-survey and was analyzed by using SmartPLS 3.0. The interview results showed that the implementation of SAIS did have an impact on the Faculty, such as increasing staff productivity and reducing costs. Moreover, the PLS-SEM analysis results showed that SAIS Service Quality positively influenced student satisfaction towards FBMSAIS implementation. This study provides an empirical validation of the SAIS Service Quality Model in the context of Higher Education